The impact to multidimensional models by the range of definition - Šaltenis, Vydūnas; Tiešis, Vytautas (Lietuvos matematikos rinkinys, 1998)
The aim of the research was to investigate ways for simplification of multidimensional models. The simplification mode based on the system of characteristics, that is similar to the dispersion analysis, was investigated. It was shown how characteristics may be used to divide the model into several more simple submodels, for example, linear models. The core of the simplification is the division of a range of definition where the characteristics serve as an indicator of accuracy and type of submodels.